Comparison of the Incidence of Nausea and Vomiting in the Administration of Tramadol 100 mg Suppositories with Intravenous Post-Spinal Anesthesia for Lower Extremity Surgery - Putra, Adhi Setia (Buletin Farmatera, 2021)
Pendahuluan :Post operative nausea vomiting (PONV) pasca pemberian tramadolPostoperative nausea vomiting (PONV) after intravenous administration of tramadol has a high incidence rate, so it needs alternative drug administration to overcome this problem. This study aims to compare the incidence of postoperative nausea and vomiting in the intravenous administration of tramadol suppositories. A double-blind analytical experimental study, involving 36 subjects divided into tramadol suppositories and intravenous tramadol post-extremity surgery with spinal anesthesia at Haji Adam Malik Hospital and Network Hospital in 2013. The incidence of PONV in tramadol suppository subjects was much lower than in intravenous tramadol subjects.